Collaborative Governance in The Menoreh Hills Tourism Area, Sedayu Village, Loano District, Purworejo Regency - Suparaman, Jaya; Mualidin, Isnaini (Universitas Muhammadiyah Yogyakarta, 2021)
In recent years, area of 309 Ha in the Menoreh hills area was establish as the authority zone under the Borobudur Authority Board (BOB) by the central government. The establishment in purpose to support the Borobudur tourism area in Magelang Regency. The present of the authority zone and BOB has changed the political dynamic and power relations as well as given influence to socio-economic, natural, and the tourism conditions. This including the change of player in the area and the diversion of the forest land must have taken into deep considerations. Though the program seems quite promising, the implementation was challenging, especially regarding sustainability. Therefore, successful and sustainable practical examples are needed. This paper analyses how far the collaboration of a case study. The main focus of this research is on how the collaboration and involvement of the related inter-organizational stakeholders have contributed to the program sustainability. Data and information for this study were obtained through in-depth interviews, observation, and documents review. This study found that the local level stakeholders are lacked in participation. Decision making and data sharing has a major role in implementing the program, among those various entities of stakeholders. Hence, the paper states this is the key to the success and sustainability of the program.